Theoretical Approaches to Process Validation in Pharmaceutical Manufacturing Process (International Journal of Scientific Research in Science and Technology, 2024)
Under the more general statutory CGMP provisions of section 501(a)(2)(B) of the Federal Food, Drug and Cosmetic Act, validation of manufacturing processes is deemed a legal part of current good manufacturing practice for active pharmaceutical ingredients (APIs). Validation of manufacturing processes is required by the Current Good Manufacturing Practice (CGMP) regulations for finished pharmaceuticals (21 CFR 211.100 and 211.110). A medication should be created that is suitable for its intended purpose, according to the fundamental tenet of quality assurance. Procedure Validation is the collection and estimation of data that proves a process can reliably produce high-quality goods, starting with process design and continuing through commercial production. Three stages of validation are suggested by the 2011 USFDA process validation guideline - Process design, Process qualification, Continued Process qualification. An introduction and broad review of process validation in the pharmaceutical manufacturing process, specifically in the tablet manufacturing process, are provided in this article. Process validation ensures that a process will consistently create a product that meets its predefined quality features and qualities. It is a crucial step in the design, prototyping, and manufacturing processes. Since quality is always a necessary precondition for any product, pharmaceuticals must be produced to the greatest standards of quality. Furthermore, end-product testing does not ensure the product’s quality on its own; rather, quality assurance methods need to be applied to incorporate the product’s quality throughout the whole process, rather than only testing it at the conclusion.